EXPLORING NEW HORIZONS: ASSESSING THE INFLUENCE OF INNOVATIVE CURRICULUM DEVELOPMENT STRATEGIES ON HIGH SCHOOL STUDENTS’ ACADEMIC PERFORMANCE AND ENGAGEMENT (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
The examples of the innovative approaches to curriculum development are project-based learning, interdisciplinary approaches, and technology enhanced instruction, which have turned out becoming imperative tools in enhancing high school education. This paper will deal with the lack of this feature of traditional curricula, which often do not encourage such values as critical thinking and intrinsic motivation by evaluating the impact of these strategies on academic performance and interest among students. The research design employed in the study is mixed-methods primary research design where both qualitative data that is provided in the form of teacher and student interviews carried in three high schools and quantitative data in the form of normalized test scores are utilized. Findings indicate that, in spite of continuing teacher training and resource demands, novelized curriculums have become very effective in improving the quality of student learning experiences and academic performance, particularly among lower-represented students. The article helps to fill the gaps in the current discourse on curriculum change by suggesting specific interventions to be implemented by the educators and policymakers who strive to establish dynamic and inclusive learning environments.